On possibilities of diagnostics and formation of picosecond electron bunches in the linear accelerator by means of an optical deflector - Dyomin, V.S.; Reprintsev, L.V.; Shendrik, V.A. (Вопросы атомной науки и техники, 2004)
The possibilities for measuring the phase charge distribution in picosecond bunches of the electron linac without application of an electron-optical chamber are discussed. It is proposed to use the measurement scheme based on the spatial scanning of the transition radiation light pulse equivalent to the electron bunch by means of a traveling-wave optical deflector. The estimations of the sensitivity and resolution of the method are given. The picosecond optical pulse trains can also be obtained by using the microwave scanning of a laser ray across the adjustable diaphragm. After amplification, the pulses can be used in microwave photo-emission guns.